Status Keberlanjutan Usahatani Padi Organik di Kabupaten Jember dan Bondowoso - Suci Cita Eka Nurhidayat; Sri Sundari; Bayu Rudiyanto (Kadiri University, 2022)
Indonesia, a tropical country, is highly suitable for agriculture. As a staple food, rice has an essential role in the national economy. Jember and Bondowoso Regencies of East Java Province are areas that produce organic rice. The difference in the production of the two regencies affects the yield of organic rice. The study was aimed to describe the condition of the sustainability of organic crop farming in Jember and Bondowoso Regency. The study method was Multi-Dimensional Scaling (MDS) to analyze the five dimensions of sustainability. The study results showed that Jember Regency's agriculture was